Market entry for wind energy: strategic approaches for the original equipment manufacturer - Zwarteveen, Jan Willem; Zawwar, Imran; Angus, Andrew (Wiley, 2021)
Wind energy is a valuable resource, but many developing and emerging economies(DEEs) are not utilizing the tremendous wind capacity available to them. This meansthere is a potential for wind turbine original equipment manufacturers (OEMs) topenetrate new markets to increase profits, and to contribute to Sustainable Develop-ment Goals. This article explores the potential triggers for wind energy diffusion andprovides the basis for inclusive market entry strategies for wind power OEMs. Indica-tions are that early wind energy path creation is driven by climate adaptation, vestedinterests in fossil fuels and hydropower, and the business case potential. A negativebusiness case potential in many DEEs formed a substantial barrier. A shift toincreased local value creation, collaboration with traditional power producers, andpromoting wind for climate adaptation are key novel inclusive market entry strategiesto open and develop new markets.
Keywords: wind energy; inclusive; market entry; strategy; original equipment manufacturer; developing and emerging economies; diffusion